2014
DOI: 10.2214/ajr.13.11272
|View full text |Cite
|
Sign up to set email alerts
|

CT Colonography Reporting and Data System (C-RADS): Benchmark Values From a Clinical Screening Program

Abstract: OBJECTIVE The CT Colonography Reporting and Data System (C-RADS) is a well-recognized standard for reporting findings at CT colonography (CTC). However, few data on benchmark values for clinical performance have been published to date, especially for screening. The purpose of this study was to establish baseline C-RADS values for CTC screening. SUBJECTS AND METHODS From 2005 to 2011, 6769 asymptomatic adults (3110 men and 3659 women) 50–79 years old (mean [± SD] age, 56.7 ± 6.1 years) were enrolled for first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 29 publications
(36 reference statements)
2
25
1
1
Order By: Relevance
“…[16, 17] The present study essentially confirms this previous figure, as 927/7952 patients (11.7%) of our total population had either C-RADS category E3 (N=202) or E4 (N=725) findings, leaving the remaining 7025/7952 patients (88.3%) without clinically relevant extracolonic findings (C-RADS category E1 or E2). Despite persistent concern for a large number of follow-up imaging studies, the actual work up rate for all reported extracolonic findings has consistently been less than 10% in large CTC series.…”
Section: Discussionsupporting
confidence: 88%
“…[16, 17] The present study essentially confirms this previous figure, as 927/7952 patients (11.7%) of our total population had either C-RADS category E3 (N=202) or E4 (N=725) findings, leaving the remaining 7025/7952 patients (88.3%) without clinically relevant extracolonic findings (C-RADS category E1 or E2). Despite persistent concern for a large number of follow-up imaging studies, the actual work up rate for all reported extracolonic findings has consistently been less than 10% in large CTC series.…”
Section: Discussionsupporting
confidence: 88%
“…[18] Of the remaining patients with findings that may be clinically relevant, a majority have extracolonic findings which are deemed likely insignificant (C-RADS extracolonic category E3), with only a small minority of patients demonstrating potentially significant extracolonic findings (C-RADS extracolonic category E4). Despite the concern for substantial numbers of required additional studies, the actual work up rate for all reported extracolonic findings has consistently been less than 10% in large CTC series.…”
Section: Discussionmentioning
confidence: 99%
“…However, CT colonography has low sensitivity for small (6–9mm) and flat lesions 101 . The technique is associated with high colonoscopy referral rates (up to 30%), and high rates of extra-colonic findings in non-cancer cases, which translate to unnecessary investigations and increased anxiety for individuals 102,103 . The costs of CT colonography, and the need for further investigation in a subset of screenees limit the usefulness of this method for population screening in most countries.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%